BENTENG TANAH, TEKNIK PEMBANGUNAN DAN PERALIHAN FUNGSINYA - Repelita Wahyu Oetomo (Berkala Arkeologi Sangkhakala, 2006)
We had know that there‟re lots of landfort in Sumatera. Theobservation indicated that they have been built since the Hindoo-Buddhist era continued on the Islam era till the colonialism ofNetherland. That landfort represented the different era and alsothe function it self, but the essence of it is as a fort area.